1996
DOI: 10.1136/bjo.80.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Corneal temperature in patients with dry eye evaluated by infrared radiation thermometry.

Abstract: Aims-The corneal temperature change following each blink was investigated in patients with dry eye using an infrared radiation thermometer. Methods-Twenty patients with dry eye and 20 normal controls were enrolled in this study. Subjects showing decreased TEROS 40 in dry eye. Since the evaporation of tears reduces the temperature of the ocular surface,9 the temperature of a dry eye may be different from normal eyes. We measured the corneal temperature and investigated the corneal temperature change following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 19 publications
5
63
1
4
Order By: Relevance
“…Although we have previously demonstrated that the T4 metrics have some utility in differentiating dry eyes vs. controls, the present study was in agreement with Fujishima et al [14] i.e., no correlation was found between OST with individual dry eye signs or symptoms.…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drsupporting
confidence: 93%
See 1 more Smart Citation
“…Although we have previously demonstrated that the T4 metrics have some utility in differentiating dry eyes vs. controls, the present study was in agreement with Fujishima et al [14] i.e., no correlation was found between OST with individual dry eye signs or symptoms.…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drsupporting
confidence: 93%
“…Ocular surface temperature (OST) measurement with infrared (IR) ocular thermography is indicative of the tear film and its stability [9,10]. Ocular thermography has been used to study DED [9,[11][12][13][14][15][16][17][18][19] with three studies reporting on its diagnostic ability [16,18,19] with inconsistent results. We have also considered the application of IR ocular thermography in screening mild to moderate DED.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature measurement of the anterior segment of the eye is of potential importance in a variety of research applications, including ocular inflammation, tear film, and photorefractive surgery [1, 2, 3, 4, 5, 6]. Because the temperature of the body surface depends largely on local blood flow, temperature measurements might also provide information on the latter, including in ocular tissues [2, 4, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Con base en lo anterior, en este trabajo se han propuesto los fundamentos basados en resultados experimentales, que permitirían posteriormente establecer un método para diagnosticar de manera cuantitativa el síndrome del ojo seco, mediante la técnica de la termografía infrarroja, el cual puede llegar a ser un procedimiento totalmente efectivo para el diagnóstico clínico del mismo (5,16,33), ya que se basa en pruebas cuantitativas, mientras que en la actualidad el diagnóstico se hace por medio de pruebas cualitativas no muy precisas como lo es la prueba Schirmer I; sin embargo se hace necesario realizar un trabajo con una muestra poblacional mayor, con el fin de cuantificar y estandarizar de manera formal el método propuesto, de tal manera que pueda ser utilizado para el diagnóstico y seguimiento clínico del SOS.…”
Section: Discussionunclassified
“…En la actualidad, el estudio de la sequedad ocular ocupa un lugar privilegiado en las investigaciones oftalmológicas, ya que los intensos esfuerzos destinados al estudio de esta singular enfermedad están orientados principalmente hacia los aspectos relacionados con su fisiopatología y el desarrollo de nuevos y efectivos medicamentos (3); por lo que se ha dejado atrás el estudio de nuevas opciones de diagnóstico totalmente cuantitativas y no invasivas. Generalmente el diagnóstico de ojo seco se basa en el desarrollo de dos pasos, la recopilación de datos a partir de las manifestaciones que el enfermo refiere, y los test de diagnóstico: Schirmer I, tiempo de ruptura de la película lagrimal (BUT), tinción con rosa de Bengala, fluoresceína o lisamina verde (3,5,6), aunque estas pruebas son utilizadas por los oftalmólogos actualmente, no son totalmente confiables ya que arrojan resultados no muy precisos y además son muy incomodas para el paciente.La termografía biomédica no es invasiva, no es ionizante, libre de riesgo, amigable con el paciente y el costo es considerablemente bajo (7). Distribuciones de temperatura de la superficie de la piel plasmadas en una imagen térmica se pueden utilizar para identificar las áreas de anormalidad térmica, para la detección temprana y monitoreo de los procesos de enfermedad; y para controlar la eficacia de los procedimientos de tratamiento (8).…”
unclassified